„Współcześni gladiatorzy”. Próba określenia istoty i kulturowego znaczenia profesjonalnego wrestlingu - Biernacik, Joanna (Załącznik Kulturoznawczy, 2018)
Professional wrestling is a polarizing phenomenon, adored for its excessive nature, yet still categorized as ‘fake’. Under the surface of a simple form of mass entertainment there are plenty of cultural contexts to be found, from the carnivalesque nature of the show itself, the stereotype issues, the subversion of standards, to its area of social transgression. This article presents sports entertainment as a multi-layered and intermedial phenomenon, especially representative of the American mass culture.